Analisis Pelaksanaan Investigasi Kontak Tuberkulosis dengan Pendekatan 5M di Komunitas Masyarakat Sehat Sriwijaya Kota Palembang - Dea Aulia Handayani; Siti Halimatul Munawarah; Rudy Chendra (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2025)
Tuberculosis is a serious health problem that needs to be resolved immediately. Palembang City has the highest TB case finding rate in South Sumatra at 7,379 cases, which is equivalent to 31.73% of the total cases in South Sumatra. Contact investigation is the main strategy in detecting new cases and breaking the chain of transmission. The Healthy Sriwijaya Community in Palembang City is an important and integral part of the implementation of contact investigations. This study aims to analyze the implementation of contact investigation using a qualitative approach, employing in-depth interviews with twelve informants using Herrington Emerson's 5M (Man, Money, Materials, Method, Machines) theory. The results showed that the implementation of TB contact investigation was not optimal. The distribution of the cadre index has not been evenly distributed due to regional constraints, difficult access and distance, sufficient funds but untimely disbursement, logistical distribution obstacles, technical reporting constraints, and rejection due to community stigma. Strengthening education and active participation of various parties are needed to increase the coverage of contact investigations.Keywords: Community, Contact Investigation, Management, Tuberculosis